2019
DOI: 10.1097/aln.0000000000002920
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Effects of Sevoflurane in Young Adult Rats

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Sevoflurane administered to neonatal rats induces neurobehavioral abnormalities and epigenetic reprogramming of their germ cells; the latter can pass adverse effects of sevoflurane to future offspring. As germ cells are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 54 publications
3
64
0
Order By: Relevance
“…Statistical details are presented in the text and figure legends. The sample sizes in this study were based on previous experience with the same experimental techniques and measured parameters (Edwards et al, 2010;Tan et al, 2014;Xu et al, 2015;Zhang et al, 2016;Ju et al, 2017Ju et al, , 2018Ju et al, , 2019. We studied the ability of sevoflurane to cause EEG-detectable seizures in the P9, P10, or P11 male rats in all four experimental groups, i.e., the control rats and rats that were exposed to sevoflurane for 6 h on P4, P5, or P6 after pretreatment with the vehicle, formestane, or bumetanide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical details are presented in the text and figure legends. The sample sizes in this study were based on previous experience with the same experimental techniques and measured parameters (Edwards et al, 2010;Tan et al, 2014;Xu et al, 2015;Zhang et al, 2016;Ju et al, 2017Ju et al, , 2018Ju et al, , 2019. We studied the ability of sevoflurane to cause EEG-detectable seizures in the P9, P10, or P11 male rats in all four experimental groups, i.e., the control rats and rats that were exposed to sevoflurane for 6 h on P4, P5, or P6 after pretreatment with the vehicle, formestane, or bumetanide.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to improve the safety of pediatric anesthesia, numerous studies have proposed various mediating mechanisms of the adverse effects of general anesthetics in neonatal animal models, further confirming the mechanistic complexity of this phenomenon ( Vutskits and Xie, 2016 ; Lin et al, 2017 ). Our approach in this field is based on an assumption that the developing brain is especially vulnerable to the deleterious effects of general anesthetics because, at least in part, the anesthetics exert their adverse effects by affecting mechanisms specific to this age period ( Edwards et al, 2010 ; Tan et al, 2014 ; Xu et al, 2015 ; Zhang et al, 2016 ; Ju et al, 2017 , 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As germ cells are susceptible to reprogramming by environmental factors across the lifespan, Martynyuk’s lab also tested whether sevoflurane could induce neurobehavioral abnormalities in offspring when the anesthetic is administered to young adult rats [ 94 ]. They found similar, not identical, abnormalities in parental germ cells and in male offspring of exposed sires and dams.…”
Section: Germline Exposure To Ga Raises Risk For Offspring Brain and mentioning
confidence: 99%
“…This phenomenon is consistent with the increased risk for male offspring pathology in intergenerational responses to GA exposure as detected in Ju et al . [ 92 , 94 ]. Additionally, other studies in chemical disruption of germ cells have found male offspring more likely suffer adverse neurobehavioral effects [ 13 ].…”
Section: Heritable Impacts Of Ga May Help Explain Findings In Autism mentioning
confidence: 99%
“…Subsequent preclinical studies demonstrated that GA caused a vast amount of acute injury and long-term cognitive impairments in rodents [6][7][8][9][10][11][12][13] and nonhuman primates (NHP) [9,10,[14][15][16][17][18][19][20][21][22][23]. Even worse, exposure to GA in neonatal rodents produced adverse effects on the learning and memory of their offspring via epigenetic modulation [24][25][26][27]. Taken together, these solid preclinical findings suggest that exposure of the developing brain to GA contributes to the long-term adverse neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 98%